Arahan Sistem Pertanian Ideal Berbasis Potensi Sumberdaya Lahan: Komponen Dasar Cukilan Smart Village - Andree Wijaya Setiawan; Bistok Hasiholan Simanjuntak; Yoga Aji Handoko; Yohanes Hendro Agus; Lasmono Trisunaryanto; Maria Maria; Adi Nugroho; Johan Jimmy Carter Tambotoh (Universitas Muhammadiyah Surakarta, 2024)
In recent years, the concept of smart villages has gained increasing prominence as a means of encouraging sustainable development in rural areas. This is particularly relevant in the agricultural sector, where the potential of land resources is crucial. Cukilan Village, located in Suruh District, Semarang Regency, Central Java, is primarily an agricultural area, with over 80% of its land designated for agricultural purposes. The village government has expressed a desire to develop Cukilan as a smart village through an FGD process. Based on this background, a community service program was implemented with the aim of designing Cukilan Village as a smart village in stages, to enhance economic growth and prosperity by leveraging the potential of agricultural resources and human resources, as well as accelerating the village development process. The method for implementing this PKM (Community Service) program utilized the Assets-Based Community Development (ABCD) approach, which involved outreach, discussion, mapping of agroecological zones, as well as land suitability and evaluation. As a result of this initiative, the Cukilan Village government received guidance for an ideal agricultural system based on land resource potential, which serves as a basic component towards the realization of Cukilan Smart Village.